Fat and Water Contents of The Muscle and Gonad of Otolithus argenteus in Relation to Gonad Growth - VINAYAK, V; NEELAKANTAN, B (Fishery Technology, 2017)
Fat and water contents of the muscles and gonads in relation to gonad growthin Otolithus argentes from Karwar are reported. Water content showed aninverse relationship to lipid in both the sexes. Variation in somatic body weightwas found associated with the fluctuations in Jjpid contents